PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS PRAKTIKUM INKUIRI UNTUK MATA PELAJARAN MENGANALISIS RANGKAIAN LISTRIK - Oriza Candra; Usmeldi Usmeldi; Doni Tri Putra Yanto; Femypadillah Ismanto (University of Muhammadiyah Malang, 2020)
The purpose of this study was to develop a valid, practical, and effective practicum-based learning tool on MRL subjects with the Magnetic Circuit material in SMKN 1 Padang consisting of RPP and LKS. This type of research is development research using a 4-D development model consisting of 4 stages, namely defining, designing, developing, and analyzing. The respondents of this study were students of class X TDTL-B SMKN 1 Padang consisting of 29 students. The results of data analysis obtained from the developed learning tools are categorized valid with the level of validity of the RPP and LKS are 85.42% and 87.50%. Learning Tools developed are categorized as practical with the practicality of teachers and students being 80% and 86.03%. The learning tools developed are effective in increasing students' competencies with classical completeness for cognitive, affective, and psychomotor competencies are 89.66%, 100%, and 100%. It can be concluded as a practicum-based learning tool developed which is a valid, practical, and effective learning tool.